Deforestation and fragmentation of Chaco dry forest in NW Argentina (1972-2007) - Gasparri, Nestor Ignacio (2009)
The sustained increase in the global food demand has favoured the recent expansion of industrial agriculture into neotropical dry forest ecosystems, with resulting changes in their extent and spatial configuration. Based on Landsat satellite images, we analyzed changes in forest cover and landscape configuration over an area of 600 by 100 km located in NW Argentina (Tucuma´n and Salta provinces) in four periods between 1972 and 2007. The study area, one of the most active deforestation frontiers of South American dry forest, was divided into six relatively homogeneous sectors in terms of land property structure and biophysical characteristics. During the study period 1.4 millions hectares of dry forest were cleared. Deforestation started in the 1970s as a result of technological changes and increasing rainfall; continued (with spatial and temporal fluctuations) during the 1980s and 1990s in association to the sustained global demand of soybean, and was accelerated (to ca. 100,000 ha year_1) between 2001 and 2007 following the global increase in commodity prices, and the national peso devaluation. We described the landscape structure using eight landscape indices, summarized as one synthesis value: the Euclidian distance across the seven dimensions from a theoretical non-fragmented situation. In areas with soil limitations deforestation resulted in relatively stable, highly fragmented landscapes. In contrast, the sites with regional coarser-scale limitations (rainfall), deforestation produced a less fragmented landscape where agriculture concentrates in sites with high rainfall. Sites with no limitations for agriculture tend to a largely deforested landscape with few small and poorly connected forest patches. The land properties size seems to influence some indices of fragmentation, but the synthetic index of fragmentation suggests an overall convergence of fragmentation patterns towards a similar configuration across different biophysical and land tenure conditions